Analisis Faktor Penghambat Komunikasi Efektif Dalam Pendidikan Di TK Swasta Al Ihsan - Yuyun Andriani; Azivah Zahrianis; Kathryn Elya Zahra (CV. ITTC INDONESIA, 2024)
His research aims to analyze what factors are obstacles to effective communication and what factors are obstacles to effective communication in the Al Ihsan private kindergarten educational environment. This research uses a qualitative research method which is a type of research methodology which in its application uses data originating from research results which are then analyzed. In this study, the research results came from interviews and also direct observation. The population and sample in this research were students and teachers at the Al Ihsan private kindergarten on Jalan Mangkara. The results of this study show that there are several factors that hinder effective communication in the educational environment, including lack of self-confidence arising from students' health problems, speech or messages that are difficult to understand, and language differences